Gingival Hyperplasia Associated with Cyclosporine and Amlodipine Administration in a Child with Nephrotic Syndrome and Regression after Therapy Correction: Clinical Case - Alina B. Strok; Maria N. Kostyleva; Anna V. Kostina (Вопросы современной педиатрии, 2025)
Background. Gingival hyperplasia is a pathological diffuse or local outgrowth of fibrous tissue in the gums and paradontium. Excessive growth of gum tissue can cause periodontal inflammation and results in tooth loss, speech and chewing issues, aesthetic changes. The described cases of gingival hyperplasia in children on cyclosporine therapy are limited by the short follow-up (up to 2 months) and do not contain data on cyclosporine levels in the blood and hyperplasia regression after treatment cessation.Clinical case description. The child, 8 years 10 months old, male, was hospitalized for nephrotic syndrome management. He was consulted by the dentist several times due to gingival hyperplasia; topical therapy had no effect. Therapy of nephrotic syndrome was revised during hospital stay. Two drugs were identified that could provoke the hyperplasia development: cyclosporine (on-treatment period — 5 years 10 months) and amlodipine (on-treatment period — 1 year 6 months). Monitoring of ciclosporin levels in blood was prescribed. Episodes of increased cyclosporine levels (above the recommended values) were recorded. The drug was considered as the most likely cause of drug-induced gingival hyperplasia. Amlodipine was considered as additive factor exacerbating the side effect. Both drugs were discontinued. Gingival hyperplasia regression was noted 9 months later at return to the clinic.Conclusion. Administration of drugs associated with high risk of gingival hyperplasia development requires dynamic follow-up for timely therapy correction and severe complications prevention.However, monitoring of ciclosporin levels does not guarantee the prevention of side effects.